Influence of Carbon - Nitrogen Supplements and pH on Growth of Sugarcane Stem rot Pathogen Fusarium Solani NVS671 - Prittesh Patel (Journal of Fungal Diversity, 2020)
Fusarium solani NVS671 identified from infected sugarcane stem of Co 671 as a new pathogen was subjected to various cultural conditions to understand its physiological profile. In continuation with our previous work, cultural analysis was carried out under in vitro condition by supplementing various carbon and nitrogen sources in Czapek-Dox agar (CDA). Under different hydrogen ion concentrations, it was found that the growth of Fusarium solaniNVS671 was less at pH 4 and pH 10 and could reach up to 5 cm after 7 days of incubation on Potato Dextrose Agar (PDA). It is observed that the pH around 7 to 8 was optimum for the growth of F. solani. Ten different nitrogenous (N) sources and nine different carbon sources were tested on CDA medium to know their effect on the mycelial growth rate and characteristics of the fungus. Among the N sources evaluated, ammonium chloride (7.96±0.11 cm) was found to be most efficient for mycelial growth promotion followed by ammonium nitrate (7.7±0.1 cm) and ammonium sulphate (7.3±0.1 cm). The most preferred carbon source recorded to promote best radial mycelial growth was starch (7.96±0.05 cm) and sucrose (7.93±0.05 cm). Capabilities of using different carbon and nitrogen sources and ability to grow at different pH levels may allow species to adapt to specific soil conditions.This study is important to understand the physiology and metabolite preference of F. solani.
Keywords: Carbon